Commanding information and communication technology - Banik, G.C. (2001)
The concept of communication today is not confined to phones, fax or teleprinters, it is much more and beyond that. This article uncovers a whole plethora of futuristic communication tools provided by satellites and information highways. Deployment of these technologies has already changed the face of communication worldwide. The author is hopeful that their adoption will herald a new era of development and competitive edge. - Reproduced
Keywords: Information technology; Communication technology